What can we learn from a peer review? - Stilling Olesen, Jesper (Outlines. Critical Practice Studies, 2021)
The quality assurance of research articles is based on a widespread reliance on peer review, which has gradually become black boxed, as the way to do it. By opening the black box, it turns out that this form of quality assurance varies a great deal. This article looks at the comments offered by peer reviewers and treats them as an important but overlooked element of the methodological circle and science production. Based on an auto-ethnographical study of one manuscript that undergoes peer reviewing in three different journals the article examines how the review comments affect the author and hence promote/inhibit the becoming of a research article. The article offers a transmethodological look at peer review by employing concepts from actor-network theory. This allows for a theoretical move from notions of single authorship to notions of writing as a performance of relations between heterogeneous actors. The analysis aims to identify the connections that are established between the manuscript and other actors such as scientific standards for good research, journals’ aim and scope, universities’ requirements for staff publication, peer reviewer’s personal academic interests etc. which all become part of a peer review network. In conclusion, the article suggests acknowledging the relational and co-productive aspect of peer reviewing as an important part of quality assurance of scientific knowledge.